Laicity in Argentina (2017) - Esquivel, Juan Cruz (2024)
In Laicity in Argentina, the author defines laicity as the autonomisation of political institutions, delivering them from religious influ-ences. This includes, but goes beyond, the separation of church and state. Esquivel sug-gests not following the well-trodden path of setting the French model as the normative standard, but instead analysing different paths towards laicity, from a historical and sociological perspective, in order to characterise its different contemporary configurations. In his broad analytical orientation, Esquivel’s approach bears similarities to the multiple secularities approach of Burchardt, Wohlrab-Sahr, and Kleine (see texts no. 21, and no. 42 in this volume).